A fotografia de Otto Stupakoff : das páginas das revistas aos museus - Silva, Paula Rafaela da (2020)
This s y w z h O S k ’ (1935-2009) trajectory and its fashion photography. Through the use of fashion photos, we sought to understand the agents, institutions, and dynamics that led fashion photography to enter museums. The main sources for the study were fashion magazines that were published by him, the books dedicated to his work, and the material displayed in the Museum of Modern Art in New York, the Museum of Art in São Paulo, Moreira Salles Institute. In dialogue with the bibliography on the history of fashion, history of photography, we problematized the technical and thematic choices of photography by Otto Stupakoff and his authorial photographic language from his experience in major fashion magazines among the 1960s and 1970s, especially at the American Harper's Bazaar. In parallel to this performance in the press, in which he developed an authorial photograph, Stupakoff sought to exhibit his work in galleries and museum exhibitions. It is understood that the institutionalization of Stupakoff's work was due to the coherence of the authorial work produced throughout his trajectory and that his photographs, when entering these museum institutions, took on new meanings. It was concluded that fashion takes on a role as a translator of these aesthetic elements and that Stupakoff, when using it as a tool to develop his aesthetics, affirmed his name in the history of Brazilian photography and opens the way for the institutional recognition of fashion photography by others professionals in the field.